A human-centred review on maritime autonomous surfaces ships: impacts, responses, and future directions - Li, Xue (2024)
Maritime autonomous surface ships (MASS) are transforming the future of maritime transport. They are expected to shoulder important roles in seaborne trade and maritime resilience. As the primary operator of traditional ships and a significant component of maritime transport, seafarers are inevitably directly and indirectly affected by levels of automation introduced into the shipping space. Therefore, in addition to increasing attention to automated system designs, a holistic understanding of human elements in MASS operations is necessary. The current research (1) reviews human-centred MASS research, (2) categorises MASS impacts on seafarers, and (3) summarises responses to prepare seafarers for this emerging technology. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, a total of 101 articles were collected from Scopus. The systematic review reveals that MASS impacts seafarers from the following dimensions: employment, task contents, requisite skills, and human risks. Moreover, regulations and education frameworks can be adapted to respond to changes in seafarer demand and supply. Future research directions are also proposed and can serve as recommendations for future human-centred research on MASS. The research findings enhance the understanding of seafarer elements in MASS operations and provide policy implications for future seafarer management.